Hybrid Lesson Study: An Innovative Model for Enhancing Pre-Service Teachers' TPACK in Indonesia's PPG Program - Darsih, Endang; Hanggara, Agie; Andhika Putra, Rizka; Palmer, Roger (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aims to investigate the implementation of Hybrid Lesson Study as a professional learning model to enhance pre-service teachers’ Technological Pedagogical Content Knowledge (TPACK) within Indonesia’s Teacher Professional Education (PPG) program. Method: A qualitative case study design was employed to explore the complex, real-life implementation of HLS within the PPG’s Teaching Practicum (PPL). Ten pre-service teachers and two supervising lecturers from two Indonesian universities participated in this study. Data were collected through classroom observations, analysis of teaching artifacts (lesson plans, digital learning materials, and reflective reports), and semi-structured interviews. Data triangulation was used to ensure validity, while thematic analysis identified recurring patterns related to TPACK development, collaboration, and hybrid learning practices. This design enabled an in-depth understanding of how HLS supported professional learning in an authentic educational context. Results: The findings reveal that Hybrid Lesson Study, combining face-to-face meetings with online collaboration, provided a flexible and sustainable framework for lesson planning, peer observation, and reflective dialogue. Participants showed notable improvement in lesson design and technology integration, moving from basic tool use to interactive, context-based, and pedagogically sound digital practices. Reflection sessions via digital platforms further enhanced critical evaluation skills and effective technology use, supported by collaboration, feedback, and institutional infrastructure. Novelty: Despite challenges such as internet instability and time constraints, the study highlights the novelty of Hybrid Lesson Study in the PPG context, offering a practical and innovative model that fosters reflective, adaptive, and technologically competent teachers for 21st-century classrooms.